Analisis Implementasi Hierarchy Value Chain Samsung dalam Persaingan Smartphone Global - Puguh Toko Arisanto; Rika Yuliana (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This article aims to examine the value chain of Samsung's smartphone business in the context of global market competition. The author will specifically focus on one aspect of value chain governance, namely the hierarchy value chain, as a strategic approach adopted by Samsung in collaboration with its suppliers. This study uses a descriptive qualitative research method by conducting literature reviews from various sources relevant to the case study being discussed. Based on the analysis conducted, the author find that Samsung decided to produce its own smartphones because they have complex product specifications, are difficult to codify, and have low supplier capabilities